California - Benson, Sara; Bender, Andrew; Bing, Alison; Brash, Celeste; Ho, Tienlon; Kohn, Beth; Skolnick, Adam; Vlahides, John A. (Lonely Planet guidebooks., 2015)
Presents a guide to California, describing accommodation, restaurants, transportation, shopping, major points of interest, and sightseeing activities.